(untitled) (Research, Society and Development, 2022)
This article aims to analyze, from integrative research, the use of MOOC (Massive Open Online Course) and active methodologies for science teaching, demonstrating their characteristics, possibilities and limitations. The research systematization is of a qualitative, exploratory type based on the Integrative Literature Review. Twelve articles indexed in the databases of the Platforms: CAPES, SciELO and Google Scholar were analyzed from 2017 to 2022. The result of the reviewed articles was consolidated in a demonstrative table where the articles are arranged in alphabetical order of the authors’ names, date and time, country of publication, journal in which they were published, indexing platform, objectives of each study, subjects involved in the research, and main conclusions of the study. A priori, the main conclusions showed that the use of the MOOC has already been widely used in Brazil, whose majority audience is university students and higher-level professionals who demonstrate a self-directed training, in addition to contributing to the continuing education of teachers. Thus, the configurations of the MOOC allow the subjects to seek a lighter, short-term training, focused on improvement, being carried out by Higher Education Institutions through virtual learning environments (VLE) that guarantee the quality of certification to the participants.